Construction of the Jakarta International Stadium and Clientelism Practices Against The Jakmania By Anies Baswedan as Presidential Candidate for the 2024 Election - Muhammad Reyhan Afif Septyatna; Abdul Ghofur (Program Pascasarjana Universitas Negeri Makassar, 2024)
Indonesian people on average have an interest in the world of sports, especially football, which is in the massive category. Even though the standard of football quality is below average, each club has a large number of fans. This article aims to analyze the Development of the Jakarta International Stadium and Clientelism Practices Toward The Jakmania by Anies Baswedan. The Jakarta International Stadium was a political promise made by Anies Baswedan during his candidacy for Governor of DKI Jakarta in 2017, which was eventually realized in 2019. With the implementation of this development, it undoubtedly serves as Anies Baswedan's political capital in the democratic contest of 2024 as a presidential candidate. This study employs qualitative research methods with structured interviews conducted with officials and members of The Jakmania. The interviewed officials of The Jakmania include the Secretary-General and Treasurer-General, who stated that Anies Baswedan is the Governor closest to The Jakmania among his predecessors. This article also explores the impact of the Jakarta International Stadium development on Anies Baswedan's presidential candidacy. Findings indicate that the Jakarta International Stadium built by Anies Baswedan has had a positive impact in terms of The Jakmania's political perspective. The results of the research align with the theoretical framework underlying this study. This research can be used as material to evaluate the level of community participation in the decision-making process regarding stadium construction.